Bridging Culture and Technology: Digital Ecotourism and Local Wisdom Sustainability - Hairunnisa Hairunnisa; Nurliah Nurliah; Kadek Dristiana Dwivayani; Dony Kristian; Husain Heriyanto (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2026)
This study discovers sustainable tourism by focusing on how digitalization is revolutionizing community-based ecotourism in rural Indonesia, particularly in Pela Tourism Village, East Kalimantan. It investigates how digital tools supercharge promotional strategies and bring local wisdom, like Mahakam dolphin conservation and traditional practices, to a global audience. This research fills critical gaps in localized ecotourism studies, where digital transformation often overlooks ties to environmental sustainability and community empowerment, while bolstering weak areas in tourism competitiveness such as ICT readiness and green practices. This research employs a qualitative descriptive approach with an intrinsic case study design. Researchers collected data via observations, interviews, and document reviews. Data were analyzed using the Miles and Huberman interactive model, covering data reduction, data display, and conclusion drawing and verification. This research confirms that digital ecotourism in Pela thrives on five key pillars: knowledge, internetworking, convergence, communication, and innovation. Platforms like Instagram, TikTok, and QR codes dramatically expand reach, foster interactive engagement, preserve heritage, and craft a strong village identity, enhancing competitiveness despite hurdles like patchy internet. This research offers tourism scholars a village-level framework blending digitalization, ecotourism, and local wisdom, proving digital strategies are vital for sustainable development by safeguarding the environment, culture, and community well-being in the digital tourism era.